2017
DOI: 10.1177/1078155217740945
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile treatment in neutropenic patients: Clinical outcomes of metronidazole, vancomycin, combinations, and switch therapy

Abstract: Background Clostridium difficile infection treatment guidelines exist for immunocompetent patients; however, there is a paucity of data evaluating clinical outcomes and time to C. difficile-associated diarrhea resolution in neutropenic patients. Objective To assess clinical outcomes in neutropenic patients treated with metronidazole, oral vancomycin, the combination of metronidazole plus oral vancomycin, and switch of metronidazole to oral vancomycin. Methods This retrospective, observational cohort study asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The neutrophil: lymphocyte ratio is a predictor for ICU admission and death within two days of CDI diagnosing 31 . Another retrospective study found a link between neutrophilia and the greater possibility of CDI resolution 32 . Considering the diversity of the WBCs subpopulations in CDI patients, the total WBCs count may not be an accurate indicator of disease severity 33 .…”
Section: Discussionmentioning
confidence: 97%
“…The neutrophil: lymphocyte ratio is a predictor for ICU admission and death within two days of CDI diagnosing 31 . Another retrospective study found a link between neutrophilia and the greater possibility of CDI resolution 32 . Considering the diversity of the WBCs subpopulations in CDI patients, the total WBCs count may not be an accurate indicator of disease severity 33 .…”
Section: Discussionmentioning
confidence: 97%
“…However, the clinical significance of neutrophil count in neutropenic patients is different, since in a small cohort of neutropenic patients the increase of absolute neutrophil count was linked to increased likelihood of resolution of CDI. 10 Therefore, the clinical implications of leukocytosis and impaired renal function as outcome indicators of CDI require detailed evaluation of clinical complexity of the care receipts.…”
Section: Discussionmentioning
confidence: 99%
“…9 In contrast, another retrospective study found that increasing neutrophil count was linked to a higher likelihood of the resolution of CDI in 44 neutropenic patients. 10 An increase in eosinophils and lymphocytes, two other important subpopulations of leukocytes, was associated with milder CDI severity. 9,11 As there were variations in the subpopulations of leukocytes among the CDI patients with at least one comorbidity and polypharmacy, total leukocyte count may not be a perfect indicator of disease severity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it was noted that patients treated with vancomycin had a shorter interval of clinical improvement than those treated with metronidazole [30]. In our center located in central Italy, we prefer the association of the two drugs as a first-line treatment for the first manifestations of CDI as suggested by previous studies which concerned in particular frail and immunosuppressed patients with high care complexity [31][32][33]. Fidaxomycin is an effective bactericidal antibiotic in the treatment of CDI with a specificity restricted to these cases with minimal impact on the intestinal microbiota [34,35].…”
Section: Mild and Moderate Diseasementioning
confidence: 99%